Pengembangan Buku Saku Bioentrepreneur Berbasis STEM untuk Meningkatkan Minat Berwirausaha dan Kemampuan Berpikir Kritis Mahasiswa Biologi FMIPA UNIMED - Rega A Rastanura Sembiring Milala; Hasruddin; Herbert Sipahutar (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to develop a STEM-based Bioentrepreneur Pocket Book that meets practicality criteria for use in learning activities for Biology students at the Faculty of Mathematics and Natural Sciences, Universitas Negeri Medan, and to examine students’ entrepreneurial interest and critical thinking skills after its implementation. The research method employed was development research using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The results indicate that the STEM-based Bioentrepreneur Pocket Book was validated by experts. The developed pocket book was proven to be practical and effective in improving students’ learning outcomes. Furthermore, the STEM-based Bioentrepreneur Pocket Book had a positive and significant impact on students’ entrepreneurial interest and was effective in enhancing their critical thinking skills. In conclusion, the STEM-based Bioentrepreneur Pocket Book is feasible to be used as instructional material to support learning and the development of students’ 21st-century skills. Keywords: Critical Thinking, Bioentrepreneur, Pocket Book, Entrepreneurial Interest